Effects of Electrolyte Additives and Nanowire Diameter on the Electrochemical Performance of Lithium‐Ion Battery Anodes based on Interconnected Nickel–Tin Nanowire Networks. Issue 7 (13th May 2021) - Omale, Joel O.; Van Velthem, Pascal; Antohe, Vlad-Andrei; Vlad, Alexandru; Piraux, Luc
Abstract : Tin‐based nanowire electrodes present desirable properties as lithium‐ion battery anodes, because they undergo volume changes without pulverization. However, they suffer from limited mass loading and propensity for surface parasitic reactions. Herein, the electrochemical performances of nickel–tin 3D‐interconnected nanowire network (NiSn 3DNWN) electrodes are evaluated with the nanowire diameters of 40, 105, and 230 nm, respectively, that attain mass loadings of up to 3 mg cm −2 . To mitigate the surface parasitic reactions, the effects of fluoroethylene carbonate (FEC) and vinylene carbonate (VC) additives are investigated as a function of the nanowire diameter and additive concentration. The results show that the FEC and VC of all compositions improve the capacity retentions and coulombic efficiencies (CEs) of the NiSn 3DNWN electrodes. In 10 vol% FEC, the electrodes demonstrate a similar capacity of ≈550 mAh g −1, but the capacity retentions after 100 cycles are 73.68%, 53.79%, and 51.70% for the 40, 105, and 230 nm NiSn 3DNWN, respectively. However, the 105 nm‐diameter nanowire electrode has the highest average CE of 96.55%. Electrochemical impedance spectroscopy and post‐cycling investigations reveal that the FEC has the most profound effect on the interfacial resistances, which is reflected in the rate performances of the tested electrodes. Abstract : High‐mass‐loading nickel–tin 3D‐interconnected nanowire network electrodes are investigated for use as lithium‐ion battery anodes. The performances of the electrodes are a function of the nanowire diameter and additive concentration, with the intermediate‐diameter (105 nm) nanowire electrodes exhibiting the best performance, due to a balance of solid electrolyte interphase growth and lithium trapping.